Imperial Crises and British Political Ideology in the Age of the American Revolution, 1763-1773 - Gilding, Ben Joseph (Université d'Ottawa / University of Ottawa, 2014)
The Seven Years’ War and the resulting Treaty of Paris of 1763 represent a watershed in British domestic and imperial histories. Not only did the war result in Britain acquiring vast new territories and rights in North America and South Asia, but it also saddled Britain with a national debt of over £140,000,000. The challenge for British politicians in the post-1763 era was not only finding a balance between the need to secure territorial gains while searching for a means to reduce costs and raise revenues to pay down the debt, but rather to do so without infringing on the constitutional rights of colonists and chartered companies. The political ramifications of the Treaty of Paris were equally important. Disputes over the terms of the Peace tore apart the Newcastle-Pitt coalition, resulting in the dissolution of the Whig Broadbottom. With the Duke of Newcastle and his allies in opposition alongside William Pitt, the political situation was thrown into turmoil. Although the confused state of politics in the short-term undoubtedly resulted in an opposition which acted, as Namier suggested, on the basis of self-interest rather than on principles, it can also be said to have provided the matrix within which historians can observe the genesis of new policies of domestic and imperial governance. It was precisely the lack of ideological identification in politics at the accession of George III that allowed British political ideologies in the age of the American Revolution to so quickly develop alongside the formulation and implementation of, as well as in the opposition responses to, the new challenges facing British parliamentarians in the governance of the Empire. This work therefore traces the development of distinct imperial ideologies among British politicians as they emerged in response to the various imperial crises of the 1760s and 1770s. Additionally, it will be shown that the new and unprecedented crises in both American and Indian affairs were brought about primarily as a means of obtaining revenues for the Treasury. The interrelated nature of the imperial problems in the east and the west, as well as the attempts of British politicians to resolve them, will be examined primarily through the policies made surrounding the article of tea.
Keywords: Britain; Politics; Empire; Colonial; America; East India Company; Debt; Ideology; Imperial Policies; American Revolution; Bengal; Westminster; Parliament